Acute posterior multifocal epitheliopathy – case report - Fryczkowski, Piotr; Kmera-Muszyńska, Maria; Prost, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Purpose: To present an atypical course of acute posterior multifocal placoid epitheliopathy. Materials and methods: 59 years-old diabetic man was seen at emergency because of a few days history of blurred vision in his right eye. Ophthalmologic examination revealed patches of blurred margine, multiple, yellowish lesions 1 – 2 dd in the fundus in both eyes. There were also lesions typical for non proliferative diabetic retinopathy like microaneurysms, dot and blot intraretinal hemorrhages and hard exudates. Optic discs and blood vessels were normal. We found peripheral drusen extending from the equator to the ora serata in both eyes. During 8 months of observation, we performed three times ophthalmologic examination, fluorescein and indocyanine green angiographies, USG A and B. No treatment was given. Conclusions: There is disagreement about the site of origin of placoid lesions, etiology and pathogenesis in acute posterior multifocal placoid epitheliopathy. In our report we agree with thesis, that the choriocapillaris are the primary site of the break. We propose, that different duration of the APMPPE and recurrences are directly proportional to the state and quality of the blood vessels. The possible explanation for longstanding lesions in our patient is diabetic damage of the capillaries in the retina and choroid.